2006
DOI: 10.1080/03630260600868097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of β-Thalassemia in the Dohuk Region of Iraq

Abstract: beta-Thalassemia (thal) is an important health problem in the Dohuk region of northern Iraq because of its high carrier rate and the frequency of consanguineous marriages. Thus, the need to establish an effective preventative program is paramount. As part of this effort, we initiated this study to determine the molecular basis of this disorder in the region. For the latter purpose, either parent of 104 registered beta-thal major/intermedia patients had their full blood counts, hemoglobin (Hb) electrophoresis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 8 publications
6
27
4
Order By: Relevance
“…This mutation is the most common β-thal mutation in many eastern Mediterranean populations, including Turkey, Lebanon, Jordan and Syria (12)(13)(14)(15)(16), and has its highest frequencies in Cyprus, but its frequency gradually decreases in countries further to the east, with a distribution pattern almost opposite to that of IVS-II-1 (15)(16)(17)(18)(19)(20). However, such a high frequency in Kurds of northeastern Iraq is not shared by those from Dohuk or Iran with frequencies of 1.9 and 6.0%, respectively, but is comparable with those reported from northwestern Iranian populations (18.0%) (8)(9)(10).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This mutation is the most common β-thal mutation in many eastern Mediterranean populations, including Turkey, Lebanon, Jordan and Syria (12)(13)(14)(15)(16), and has its highest frequencies in Cyprus, but its frequency gradually decreases in countries further to the east, with a distribution pattern almost opposite to that of IVS-II-1 (15)(16)(17)(18)(19)(20). However, such a high frequency in Kurds of northeastern Iraq is not shared by those from Dohuk or Iran with frequencies of 1.9 and 6.0%, respectively, but is comparable with those reported from northwestern Iranian populations (18.0%) (8)(9)(10).…”
Section: Discussionsupporting
confidence: 67%
“…Northeastern Sulaimaniyah Province borders western and northwestern provinces in Iran, and therefore, it is not unexpected that the IVS-II-1 mutation is the most frequent mutation identified in our patients, since it is also the predominant mutation among Iranian Kurds and northwestern Iranians ( Table 2) as well as most other parts of Iran (7)(8)(9). Furthermore, IVS-II-1 was found to be the predominant mutation in Kurds of Dohuk in northern Iraq bordering Turkey (10). However, such high rates are shared neither by Kurdish Jews (11), the population of Diyarbakir in southern Turkey (who are mainly ethnic Kurds as well), nor by the population of East Anatolia in southeastern Turkey where the frequency is even less (12,13).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The IVS-I-6 (T→C) mutation is one of the most common causes of β-thalassemia among individuals of Mediterranean and Middle Eastern ancestry [39,40]. Its high incidence has been reported among populations from Portugal [41]; Spain [42,43]; Albania [44]; the region of former Yugoslavia [45,46,47,48]; Greece [49,50,51,52]; Algeria [53]; Egypt [54]; Palestine [55,56]; Lebanon [57]; Syria [58,59]; Cyprus [60]; Turkey [61,62,63,64,65]; Saudi Arabia [66,67]; Iraq [68,69,70,71]; Iran [72,73,74]; and elsewhere. It results from a base substitution close to the 5′ splice junction, between exon I and intron I, and within a conserved consensus sequence, interfering with mRNA splicing and, consequently, reducing its efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Among the other service indicators for prevention, it was estimated that 5/1,000 couples would be at risk of having affected children with major hemoglobinopathies, with an estimated annual birth rate of 39 affected children [5]. Other studies revealed that 8 different β-thal mutations are responsible for the large majority of cases [10,11]. Service indicators for patients' care, on the other hand, showed a total number of 845 registered patients with major hemoglobinopathies at the thal care center.…”
Section: Introductionmentioning
confidence: 99%